2022
DOI: 10.7759/cureus.29346
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of Honey Consumption With Anti-Cough Medication in Pediatric Patients: A Systematic Review

Abstract: Coughing is one of the most prevalent symptoms in children presenting at outpatient departments. This systematic review aimed to review previous literature in order to compare the use of honey and antitussive medications for treating coughs in children. Literature was screened across five databases using Medical Subject Heading (MeSH) strategy, keywords, and inclusion and exclusion criteria. The remaining literature was evaluated using a quality appraisal tool checklist. This review includes systematic reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These results confirm what is reported in the literature. Several studies have already shown the harms of cough suppressants in pediatrics [2,[6][7][8]10,13,[19][20][21][22]. As noted above, the use of cough suppressants is already prohibited in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm what is reported in the literature. Several studies have already shown the harms of cough suppressants in pediatrics [2,[6][7][8]10,13,[19][20][21][22]. As noted above, the use of cough suppressants is already prohibited in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that honey possesses pharmacological activities in humans including antimicrobial, anti-inflammatory, antioxidative, wound healing, and oral health effects. , Honey has also been used as a folk remedy for cough. A recent systematic review and meta-analysis has concluded that honey was superior to usual care for the improvement of symptoms of upper respiratory tract infections, including cough frequency and cough severity. …”
Section: Introductionmentioning
confidence: 99%
“…The combined organic layers were washed successively with saturated aqueous NaHCO 3 , water, and brine, dried, and concentrated. The residue was chromatographed on silica gel (n-hexane−ethyl acetate = 10:1 → 4:1 → 2:1) to give 6 (1.23 g, 82%) as a syrup; 1 (7). A solution of 6 (1.51 g, 5.91 mmol) in acetic acid−tetrahydrofuran−water (4:4:1, 18 mL) was stirred at rt for 2 h. After addition of powdered NaHCO 3 , the resulting mixture was diluted with water and extracted with ethyl acetate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On day 3 of treatment, there was a small reduction in cough intensity and day-time cough frequency, but in the absence of a placebo comparison these benefits are unconvincing 8. Arguably, honey may be both safer and more effective: a systematic review reported efficacy in children over 1 year of age (honey should be avoided in infants due to risk of botulism), particularly during the first 3 days of symptom onset, compared with no benefit from OTC cough remedies 9…”
mentioning
confidence: 99%